Micrographical analysis of growth deformities in common pathogens induced by voucher fungi from India. Issue 4 (December 2016) - Borthakur, Madhusmita; Joshi, Santa Ram
Abstract: A vast diversity of microbes including macrofungi remain untapped for valuable bioactivities including antimicrobial activity. Searching wild sources may bring novel natural products with antimicrobial properties that can provide protection against infectious diseases. The present study was designed to identify the diverse forms of mushrooms being used as an ethnomycological source of food and medicine by the tribes of Meghalaya, India, and microscopically study the structures of mushrooms along with observing their antimicrobial effects on pathogens. Fruiting bodies of mushrooms were viewed morphologically and microscopically, and were identified using molecular markers. The dried aerial parts of the fruiting bodies were extracted with methanol and screened for their antimicrobial activity using 2, 3, -triphenyl tetrazolium chloride against two Gram-negative and two Gram-positive bacteria. The average diameter of the inhibitory zone induced by fungal extracts ranged from 9 mm to 22 mm for Gram-negative and from 16 mm to 24 mm for Gram-positive bacteria, indicating that this dietary source is a good antimicrobial agent. Mushroom structures were examined using optical microscopy, while the deformities on the pathogens inflicted by mushroom extracts were visualized using scanning electron microscopy, which showed accumulation and formation of biofilm in Gram-positive and shrinkage with cavity formation in Gram-negative bacteria.